Polychlorinated naphthalenes in air and snow in the Norwegian Arctic: a local source or an Eastern Arctic phenomenon? - Herbert, BMJ; Halsall, CJ; Fitzpatrick, L; Jones, KC; Lee, RGM; Kallenborn, R.; VILLA, SARA (Science of The Total Environment, 2005)
PCNs were measured in air and snow during separate field campaigns at Ny-2lesund (April 2001) and Tromsb (February/ March 2003) in the Norwegian Arctic. Air concentrations ranged from 27 to 48 and 9 to 47 pg PPCN m 3 for Ny-Alesund (n=6) and Tromsb (n=10), respectively. These concentrations (including the tri-chlorinated naphthalenes) greatly exceeded concentrations previously measured in the Canadian Arctic, but did fall within the upper range of concentrations observed over the eastern Arctic Ocean and regional seas. Local sources appear to be affecting concentrations observed at both sites, with the presence of several hexa-chlorinated naphthalenes at Tromsb probably attributed to local/regional sources. Use of air mass back trajectories at Tromsb revealed that background air concentrations in the Norwegian Arctic are likely to range between b 9 and 20 pg PPCN m 3 and that contemporary concentrations derived close to potential sources (i.e. arctic towns) may equal or exceed those of PCBs. The mean concentration in surface snow was 350 and 240 pg PPCN L 1 (meltwater) (or 0.014 and 0.01 pg g 1 (snow)) at Ny-2lesund and Tromsb, respectively. The wide variation in concentrations observed between fresh snowfalls could be explained by different snow densities (as a surrogate of snow surface area), rather than attributed to varying air concentrations. A statistically significant inverse relationship was found between snow density and concentrations of tri- to penta-chlorinated homologues and compliments similar findings for the polychlorinated biphenyls (PCBs). This suggests that the vapour-sorbed quantity changes rapidly with snow ageing/compaction; with implications for the fate of these chemicals in the Arctic.